Affective Tendencies of Science Teachers in Teaching Socioscientific Issues - Meryem Hatun Elbahan; Haluk Elbahan; Burcu Anilan (Universitas Pendidikan Indonesia, 2022)
This study aims at identifying the intrinsic affective tendencies of science teachers in teaching socioscientific issues (SSI) based on different variables and their personal perspectives. The participants of the study consisted of 394 science teachers who taught at public schools during the 2021 and 2022 academic years. Regarding the research method, a mixed method that combined quantitative and qualitative research methods was employed in this study. Quantitatively, the